Update on the treatment of musculoskeletal manifestations in chikungunya fever: a guideline - Carlos Alexandre Antunes de Brito; Cláudia Diniz Lopes Marques; Melissa Barreto Falcão; Rivaldo Venâncio da Cunha; Fabrice Simon; Lilian David de Azevêdo Valadares; Kléber Giovanni Luz; Carlos Frederico Campelo de Albuquerque e Melo; Dalcy de Oliveira Albuquerque Filho; Marina Coelho Moraes de Brito; Ângela Luzia Branco Pinto Duarte (2020)
Since the emergence of the chikungunya virus in Brazil in 2014, more than 700,000 cases have been reported throughout the country, corresponding to one-third of all cases reported in the Americas. In addition to its high attack rates, resulting in hundreds of thousands of cases, the disease has high chronicity rates with persistent joint manifestations for more than 3 months, which can spread to more than half of the patients affected in the acute phase. Pain associated with musculoskeletal manifestations, often disabling, has an effect on patients' quality of life at different stages of the disease. Currently, the challenge faced by specialists is identifying the best therapy to be instituted for symptom relief despite the limited number of published intervention studies. In 2016, a multidisciplinary group published pharmacological treatment protocols for pain in patients with chikungunya, which was incorporated into the guidelines for clinical management of the Brazilian Ministry of Health in 2017; in that same year, a consensus was published by the Brazilian Society of Rheumatology about diagnosis and treatment. After 5 years of experience with chikungunya epidemics, in 2019, specialists involved in the protocols of the Brazilian Society of Rheumatology and Brazilian Ministry of Health prepared an update with the main objective of developing flowcharts for the therapeutic approach of musculoskeletal manifestations in adult patients to enable specialists at different levels of healthcare to spread and apply this guideline in a systematic and simplified manner.